Barriers to delivering advanced cancer nursing: a workload analysis of specialist nurse practice linked to the English National Lung Cancer Audit - Stewart, Iain; Leary, Alison; Tod, Angela; Borthwick, Diana; Khakwani, Aamir; Hubbard, Richard; Beckett, Paul; Tata, Laila (Elsevier, 2018)
Purpose: Health services across the world utilise advanced practice in cancer care. In the UK, lung cancer nurse specialists (LCNS) are recognised as key components of quality care in national guidelines, yet access to LCNS contact is unequal and some responsibilities are reportedly left undone. We assess whether any variation in working practices of LCNS is attributable to factors of the lung cancer service at the hospital trust. Method: Nationwide workload analysis of LCNS working practices in England, linked at trust level to patient data from the National Lung Cancer Audit. Chi-squared tests were performed to assess whether patient contact, workload, involvement in multidisciplinary teams (MDT), and provision of key interventions were related to 1) the trust's lung cancer service size, 2) LCNS caseload, 3) anti-cancer treatment facilities and 4) lung cancer patient survival. Results: Unpaid overtime was substantial for over 60% of nurses and not associated with particular service factors assessed; lack of administrative support was associated with large caseloads and chemotherapy facilities. LCNS at trusts with no specialty were more likely to challenge all MDT members (80%) compared with those at surgical (53%) or chemotherapy (58%) trusts. The most frequent specialist nursing intervention to not be routinely offered was proactive case management. Conclusion: Working practices of LCNS vary according to service factors, most frequently associated with trust anti-cancer treatment facilities. High workload pressures and limited ability to provide key interventions should be addressed across all services to ensure patients have access to recommended standards of care.